Gut microbiota modulation: a key determinant of atopic dermatitis susceptibility in children - Tang, Huimiao; Li, Wenxin; Xu, Yidan; Zhou, Yanjun; Hamblin, Michael R.; Wen, Xiang (Frontiers in Microbiology, 2025)
Atopic dermatitis is a chronic inflammatory skin condition with a higher incidence rate among children. In recent years, the role of the gut microbiota in the pathogenesis of atopic dermatitis has garnered increasing attention. This review systematically delineates the research advancements in the structural characteristics of the gut microbiota in children with atopic dermatitis and its influencing factors. Studies have revealed significant differences in the gut microbiota structure between children with atopic dermatitis and healthy controls, characterized by a reduction in microbial diversity, a decrease in beneficial bacteria, and an increase in harmful bacteria. Dietary patterns, environmental factors, birth patterns, antibiotic use, and gestational diabetes mellitus are factors could impact the gut microbiota hence influencing the susceptibility of children to atopic dermatitis. Moreover, this review explores the interplay between the gut microbiota and the immune system in atopic dermatitis, with the potential to inform more effective probiotic treatment strategies for children with atopic dermatitis.